Effect of Steamed Cake Substituted with Okra (Abelmoschus esculentus) Flour on Total Cholesterol and LDL Levels in Hypercholesterolemic Rats - Febriyatna, Ayu; Agustin, Firda; Putri Damayati, Ratih; Tiara Tsani, Sabrina; Zahrul Rusly, Mochammad (Jurnal Kesehatan Prima, 2025)
Hypercholesterolemia is a condition characterized by elevated total cholesterol levels above 200 mg/dL, which serves as a primary risk factor for cardiovascular disease. Efforts to control cholesterol levels can be achieved through the consumption of functional foods high in fiber, one of which is steamed cake made with okra flour substitution. This product contains 5.34 grams of fiber per 100 grams, thereby meeting the claim as a fiber source. This study aims to analyze the effect of okra cake administration on total cholesterol and LDL levels in male Wistar rats with a hypercholesterolemia model. The study design used was a true experimental design with a pretest-posttest control group. A total of 18 rats were divided into three groups: negative control (K-), positive control (K+), and treatment (P), each consisting of six rats. Hypercholesterolemia induction was performed for 21 days using a high-fat diet (HFD). The treatment group was then given okra cake at a dose of 8.4 g/rat/day for 14 days. The results showed that total cholesterol levels in the treatment group decreased significantly (p=0.018), while in the positive control group, there was a significant increase (p=0.000). For LDL levels, no significant differences were found in each group before and after treatment (p>0.05), but there were significant differences between the K+ and P groups (p=0.027), as well as significant differences in cholesterol levels between the K+ and P groups (p=0.016). Conclusion: Steamed cake with okra flour substitution has the potential to significantly reduce total cholesterol and LDL levels in hypercholesterolemia rats.